Soybean productivity in Rhodic Hapludox compacted by the action of furrow openers - Robson Gonçalves Trentin; Alcir José Modolo; Thiago de Oliveira Vargas; José Ricardo da Rocha Campos; Paulo Fernando Adami; Murilo Mesquita Baesso (Acta Scientiarum. Agronomy, 2018)
The heavy traffic of machines in no-tillage systems causes problems as soil compaction and loss of crops productivity. The objective of this paper is to evaluate the productivity of soybeans in reference to furrow openers and the levels of soil compaction in two crops. The experiment was conducted on Rhodic Hapludox by tracing random blocks with subdivided parcels. The soil bulk density levels were laid out in the parcels (1.16, 1.20, 1.22, and 1.26 Mg m-3) and the furrowers in the sub-parcels (double disc and shanks). The resistance to penetration, depth of the furrow, mobilized soil area, final plant stands, height of plants, mean number of beans by pod, 1,000 bean mass, number of pods per plant and productivity of the culture were evaluated. The resistance to penetration increased with the levels of soil compaction regardless of the farming year and up to a depth of 0.20 m. In the first crop, higher productivity with the use of the shank was observed. In the second crop, the use of the shank resulted in an increase in depth of the furrow, mobilized soil, height of the plants and final stand of the plants, but this did not indicate an increase in productivity.